A Review of Research Conducted with Probiotic E. coli Marketed as Symbioflor. (22nd November 2016) - Beimfohr, Claudia
Abstract : This review article summarizes the scientific literature that is currently available about a probiotic E. coli that is known under the name Symbioflor E. coli . The probiotic is marketed for human use and has been subjected to over 20 years of scientific research. As is presented here, the available literature not only contains multiple works to investigate and analyse the probiotic activity of this E. coli, but also describes a variety of other research experiments, dealing with a surprising and interesting range of subjects. By compiling all these works into one review article, more insights into this interesting probiotic E. coli were obtained.